Associations between stress and migraine and tension-type headache: Results from a school-based study in adolescents from grammar schools in Germany - Milde-Busch, Astrid; Blaschek, Astrid; Heinen, Florian; Borggräfe, Ingo; Koerte, Inga; Straube, Andreas; Schankin, Christoph; von Kries, Rüdiger (Cephalalgia, 2011)
Introduction: Stress is considered the major contributor to migraine and tension-type headache in adolescents. Previous studies have focused on general stressors, whereas the aim of the present study was to investigate associations between individuals’ stressful experiences and different types of headache. Methods: Adolescents from 10th and 11th grades of grammar schools filled in questionnaires. Stressful experiences were measured with the Trier Inventory of Chronic Stress. Type of headache was classified according to the International Classification of Headache Disorders. Linear regressions, adjusted for sex and grade, were calculated to estimate differences in stress scores that can be attributed to migraine, tension-type headache or miscellaneous headache. Results: A total of 1260 questionnaires were analysed. Tension-type headache, migraine and co-existing migraine plus tension-type headache were found in 48.7%, 10.2% and 19.8% of the participants. In subjects with migraine or co-existing migraine plus tension-type headache, high increases in stress scores were found in all investigated dimensions, whereas much weaker and inconsistent associations were found in subjects with tension-type headache only. Conclusions: The characteristic of migraine is more associated with stressful experiences than this is the case for tension-type headache. This suggests that adolescent migraine patients might especially benefit from behavioural interventions regarding stress.